UPAYA DALAM PENEGAKAN DISIPLIN/KODE ETIK ANGGOTA POLRI (Studi Di Polres Kutai Timur) - Padilan, Ferry (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe police force is one of the law enforcement officers who are always at the forefront in protecting, serving and protecting the community. In carrying out their duties it is not easy to deal with problems that are in society,Violations of the code of ethics or other forms of violations commonly practiced by members of the Indonesian National Police ie leaving the duty illegally while a National Police leaves work without a reason then a member of the National Police commits a criminal offense of insulting a woman or money laundry, violating the oath of the Police's pledge which must always be obedient to Pancasila and obey the laws.In imposing sanctions on members of the Indonesian National Police, in addition to paying attention to written legislation, it should also pay attention to General Principles of Good Governance (AAUPB).Â Keywords: Discipline Enforcement. Code of Ethics, National Police